2021
DOI: 10.1371/journal.pgen.1009670
|View full text |Cite
|
Sign up to set email alerts
|

On cross-ancestry cancer polygenic risk scores

Abstract: Polygenic risk scores (PRS) can provide useful information for personalized risk stratification and disease risk assessment, especially when combined with non-genetic risk factors. However, their construction depends on the availability of summary statistics from genome-wide association studies (GWAS) independent from the target sample. For best compatibility, it was reported that GWAS and the target sample should match in terms of ancestries. Yet, GWAS, especially in the field of cancer, often lack diversity … Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1

Citation Types

4
36
0

Year Published

2022
2022
2024
2024

Publication Types

Select...
5
2
1

Relationship

0
8

Authors

Journals

citations
Cited by 44 publications
(40 citation statements)
references
References 31 publications
4
36
0
Order By: Relevance
“…The extent to which our results can be applied to larger non-European ancestries, in particular African ancestry, warrants further investigation. These results also highlight the urgency of developing novel cross-ancestry PRS methods 10,17,53,54,55 and using more diverse cohorts to construct PRSs. 17 In addition, as the case-control and cohort analyses are derived from the same study, more broad generalizability of the results requires further investigation.…”
Section: Discussionmentioning
confidence: 77%
“…The extent to which our results can be applied to larger non-European ancestries, in particular African ancestry, warrants further investigation. These results also highlight the urgency of developing novel cross-ancestry PRS methods 10,17,53,54,55 and using more diverse cohorts to construct PRSs. 17 In addition, as the case-control and cohort analyses are derived from the same study, more broad generalizability of the results requires further investigation.…”
Section: Discussionmentioning
confidence: 77%
“…We used the nested and full models as described in Martin et al [1] to evaluate the concordance of the polygenic score with actual phenotypes. The full linear model was given as: phenotype ~PGS + age + age 2 + sex + sex � age + sex � age 2 + PC (1)(2)(3)(4)(5)(6)(7)(8)(9)(10) and the nested model contained all covariates as full, excluding PGS. R 2 attributed to PGS was estimated as the difference between R 2 of the full and the nested models.…”
Section: Plos Onementioning
confidence: 99%
“…Over the last decade, genome-wide association studies (GWAS) have discovered a substantial number of associated variants for many complex traits. Yet, the non-uniform representation of populations in genetic studies considerably limits the applicability of GWAS-based resources for individual risk prediction [1][2][3][4]. For example, Martin et al [1] showed that polygenic scores (PGS) are far more accurate for European individuals than for non-Europeans.…”
Section: Introductionmentioning
confidence: 99%
“…A similar analysis can be performed using machine learning, as illustrated in this manuscript. PRS is a more substantial quantity than classification in machine learning because PRS predicts a particular person's tendency to have a specific disease or trait [6,7]. In contrast, machine learning classifies people into traits or categories [8].…”
Section: Introductionmentioning
confidence: 99%
“…This table shows which operations can be skipped for machine learning (Step number: 3.1,3.2,3.3,3.4). Secondly, it shows the alternative of PRS calculation steps for machine learning classification (Step number: 4,5,5 1,6). …”
mentioning
confidence: 99%